Analyzing the trend of government support for cloud computing usage in e-government architecture - Muhammad Younus; Eko Priyo Purnomo; Achmad Nurmandi; Dyah Mutiarin; Halimah Abdul Manaf; Fathiya Mumtaz; Tiara Khairunnisa (Journal of Cloud Computing: Advances, Systems and Applications)
Abstract The revolution in improving services to the community carried out by the current government is genuine. It is not easy for government organizations, especially local governments, to directly implement e-government services in full. One solution that is considered appropriate and can solve these problems is the application of cloud computing to support e-government services in local governments. The advantage of cloud computing for e-government is that it can increase security. In contrast, cloud-based storage can be valuable because data stored in cloud computing is guaranteed secure and various regulations and standards of information safety practices. We propose a systematic literature review approach to analyze trends in studies on cloud computing of e-government. This research is a type of descriptive qualitative research using a bibliometric approach. To assess the trend of cloud computing in e-government, we use CiteSpace’s latest bibliometric software to achieve a comprehensive knowledge overview of cloud computing in e-government. The Findings of this paper reveal a dynamic scenario influenced by advancing technological progress and administrative priorities. Across the globe, governments are progressively acknowledging the capacity of cloud computing to improve the effectiveness, accessibility, and scalability of e-government services. Overall, challenges persist, spanning from concerns regarding data safekeeping and privacy, but it also signifies a strategic transition towards harnessing digital technologies to provide more agile, citizen-focused public services.